Management of Religious Activities at Thoyyibah Mosque, Banyuanyar - Fathonah Nurul Hasanah; Mohammad Zakki Azani (Eduvest - Journal of Universal Studies, 2024)
This research aims to determine and describe the management of religious activities, along with the supporting and inhibiting factors of religious activities carried out at the Thoyyibah Banyuanyar Mosque. This research is qualitative, using a phenomenological research approach. The data sources in this research use primary and secondary data sources. The primary data sources referred to are the chairman of the takmir and the missionary of the Thoyyibah Mosque, while the secondary data sources are data in the form of documents. The data analysis technique in this research uses the analysis model according to Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this research uses two types of triangulation, namely source triangulation and technique triangulation. The results of this research show that there are various kinds of religious activities carried out at the Thoyyibah Mosque, including routine recitations and community markets, while strengthening its activities by carrying out management functions including planning, organising, implementing, and supervising. The supporting factors for managing religious activities include funding sources, the strategic location of the mosque, community enthusiasm, and cooperation with mosque administrators. The inhibiting factors are the mosque's parking space, which is not spacious enough, and mosque youth, who do not contribute enough to participate in activities.